First record of two slug mite species of the genus Riccardoella Berlese (Acari: Ereynetidae) in Serbia (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2017)
The paper presents the first data on slug mites Riccardoella (Riccardoella) limacum (Schrank)and R. (Proriccardoella) oudemansi Thor (Acari: Ereynetidae) in Serbia. The two parasitic specieswere detected on seven species of snails and slugs (Gastropoda, Pulmonata) in Serbia.Riccardoella limacum, which is a specialized snail parasite, was found in Helix pomatia L. andH. lucorum L species of the family Helicidae. Riccardoella oudemansi was found exclusively onslug species: Arion lusitanicus Mabille (Arionidae), Tandonia budapestensis (Hazay) (Milacidae),Limacus flavus (L.), Limax maximus L. and L. cinereoniger Wolf (Limacidae).
Keywords: Snails; Slugs; Mites; Parasites